ТАРИХИЙ ТОПОНИМЛАРНИНГ ШАКЛЛАНИШИДА АПЕЛЛЯТИВЛАРНИНГ ЎРНИ (Scientific journal of the Fergana State University, 2023)
This article deals with the role of appellatives in the formation of historic toponyms.